What determines contribution to a common fund for upkeep of water infrastructures? Evidence from experimental game in Coastal Bangladesh - Buisson, Marie-Charlotte; Das, Arijit; Mukherji, Aditi (2013)
This interactive poster was presented at the 2013 Stockholm World Water Week. It describes the results of a 'public good game' carried out with farmers in the polder zones of coastal Bangladesh in order to understand determinants of contributions to maintain a public good.